Control of turbulent transport in supercritical currents by three families of hairpin vortices - Salinas, Jorge Sebastián (2021)
We elucidate the turbulent structure of supercritical gravity currents by means of highly resolved simulations that employ up to a billion grid points. Three families of hairpin vortices dominate the near-bed and interface layers of the current, with their generation mechanisms dictating their shape, orientation, and number density. The interaction of near-bed and lower-interface hairpins explains the weak inviscid lidlike behavior of the streamwise velocity maximum, while the upper-interface vortices are responsible for the substantially lower entrainment compared to turbulent wall jets.